Beberapa Metode Menulis Kalimat di Kelas Rendah - Aprilistia Nugraheni; Della Aprilyana; Diah Puri Widyawati; Tasya Putri; Dinda Zahra Ummami; Bayu Purbha Sakti (CV. ITTC INDONESIA, 2025)
Writing skills are one of the essential skills in learning Indonesian in elementary schools. However, the reality shows that many students still have difficulty in writing sentences correctly and effectively. This article examines five learning methods, namely the dictation method, writing exercises, syllabus, Think Talk Write, and picture media, with the aim of improving students' sentence writing skills. The results of literature research show that each method has its own advantages and significantly helps the development of students' writing. This article recommends that teachers use methods that are appropriate to the characteristics of students and the learning context.